Prediction of incidence and bio-psycho-socio-cultural risk factors of post-partum depression immediately after birth in an Iranian population - Abdollahi, Fatemeh (Arch Med Sci, 2016)
INTRODUCTION: Post-partum depression (PPD) is the most prevalent mental problem associated with childbirth. The purpose of the present study was to determine the incidence of early PPD and possible relevant risk factors among women attending primary health centers in Mazandaran province, Iran for the first time. MATERIAL AND METHODS: A longitudinal cohort study was conducted among 2279 eligible women during weeks 32–42 of pregnancy to determine bio-psycho-socio-cultural risk factors of depression at 2 weeks post-partum using the Iranian version of the Edinburgh Postnatal Depression Scale (EPDS). Univariate and hierarchical multiple logistic regression models were used for data analysis. RESULTS: Among 1,739 mothers whose EPDS scores were ≤ 12 during weeks 32–42 of gestation and at the follow-up study, the cumulative incidence rate of depression was 6.9% (120/1,739) at 2 weeks post-partum. In the multivariate model the factor that predicted depression symptomatology at 2 weeks post-partum was having psychiatric distress in pregnancy based on the General Health Questionnaire (GHQ) (OR = 1.06, (95% CI: 1.04–1.09), p = 0.001). The risk of PPD also lower in those with sufficient parenting skills (OR = 0.78 (95% CI: 0.69–0.88), p = 0.001), increased marital satisfaction (OR = 0.94 (95% CI: 0.9–0.99), p = 0.03), increased frequency of practicing rituals (OR = 0.94 (95% CI: 0.89–0.99), p = 0.004) and in those whose husbands had better education (OR = 0.03 (95% CI: 0.88–0.99), p = 0.04). CONCLUSIONS: The findings indicated that a combination of demographic, sociological, psychological and cultural risk factors can make mothers vulnerable to PPD.